Haircare Practice and Dandruff Problems Among Indonesian Medical Students - Wikanto, Jessica Rosemary; Wijaya, Lorettha; Astiarani, Yunisa; Regina, Regina (UI Scholars Hub, 2022)
Background: Dandruff is an understated hair and scalp problem that causes striking social and concentration issues among medical students. Haircare practice among them may or may not be related to the dandruff incident. Methods: A cross-sectional study was conducted on 74 pre-clinical medical students at Atma Jaya Catholic University of Indonesia. Trained health staff assessed dandruff prevalence by physical examination, and the haircare practice was measured using a questionnaire. Bivariate analysis was utilized to assess the association between haircare practice and dandruff prevalence’s. Result: Among respondents, 85.1% of them have dandruff. Respondents who shampooed less than five times a week, combed their hair more than seven times a week, did not use hair care and styling products were associated with higher dandruff prevalence (p Conclusion: There was a significant association between haircare practice and dandruff in medical students.